Analisis Motivasi Konsumen Terhadap Keputusan Pembelian Studi Kasus Penggunaan Tisu Tessa pada PT Graha Kerindo Utama Cabang Bogor - Zuhdi, Saefudin; Mardinah, Mardinah (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2011)
Purchasing reduplication very need in a product sale especially so that consumer always permanent use our product, oftentimes company to ignore to the effect that this, it is better company also always evaluate all changes in consumer behaviour so that permanent motivate towards tissue use tessa, rivalry that in producers industrial this time very tight is making producers in concurrence to compete are developping superiorities compete it. tissue tessa has superiority in paper quality and use benefit that follow trend present day. This watchfulness are detects consumer motivation that given towards tissue tessa, consumer confidence in use tissue tessa, consumer evaluation after use tissue tessa, and between confidence and consumer evaluation towards purchasing decision in tissue use tessa that produced by PT. Graha Kerindo principal branch Bogor. This watchfulness method uses attitude model method fishbein. model used to measures confidence and consumer evaluation formed in consumer self so that can motivate to decide a purchasing. Watchfulness result shows that consumer motivation towards tissue tessa very good. use benefit and not torn easy is superiority compete than brand tissue other chalenge, this watchfulness prove that tissue consumer has given good evaluation in tissue tessa most of benefit side and paper quality that make tissue tessa not torn easy. Evaluation result in this watchfulness shows that besides consumer feels satisfaction in tissue use tessa, also very wish for safe taste towards product doesnt contain whitener. with superiority existence competes tissue tessa, make a big opportunity in development and tissue sale tessa in the future.